Using information and communication technologies to disseminate and exchange agriculture-related climate information in the Indo-Gangetic Plains - Craufurd, Peter Q.; Balaji, V. (2014)
This report documents and analyses emerging trends in the delivery and exchange of climate information in institutionalized agricultural extension systems, as well as through information and communication technologies for development (ICT4D) efforts that have a rural–agricultural focus. Such an analysis aims to give a clearer indication of how to best direct potential future investments in sharing climate change information with noninstitutional stakeholders.